Territorialization as a tool for diagnosing the health situation: an experience report (Revista Científica Integrada, 2025)
Objective: To report the experience of the territorialization process as a diagnostic tool in Health Care, culminating in the creation of a risk and social vulnerability map of the reference unit. Method: This is a descriptive study, of the experience report type, developed in a Basic Health Unit during the month of April 2025, based on the insertion of residents from a Multiprofessional Residency Program in Family Health. Territorialization was conducted with the support of Community Health Agents, using direct observation, home visits, collection of secondary data from various sources and the Citizen's Electronic Health Record, in addition to the creation of digital maps based on Google Maps. Sociodemographic, epidemiological variables and health conditions were considered, systematized and presented to the unit's teams. Results: The survey identified 16 micro-areas distributed among three Family Health teams, with 13,186 registered users. Of these, 7.9% were hypertensive, 3.1% diabetic, 0.2% bedridden, in addition to records of leprosy (0.06%) and tuberculosis (0.07%). The analysis revealed a predominance of adults (61.3%), followed by young people (29.5%) and the elderly (9.2%), highlighting a lack of actions aimed at the adolescent public, and emphasizing the number of children with Autism Spectrum Disorder and neurodivergences. Conclusion: The implementation of territorialization made it possible to identify vulnerabilities and potentialities of the territory. In addition to supporting the planning of situational health diagnosis, assisting management and professionals in the development of their clinical practices and technical skills aimed at equity, improving health indicators of the territory.
Keywords: Health Situation Diagnosis; Family Health Strategy; Territorialization of Primary Care; Collective Health